Beyond early initiation: A qualitative study on the challenges of hospital-based postpartum breastfeeding support. - Mai-Lei Woo Kinshella; Sangwani Salimu; Marianne Vidler; Mwai Banda; Elizabeth M Molyneux; Queen Dube; David M Goldfarb; Kondwani Kawaza; Alinane Linda Nyondo-Mipando (Public Library of Science (PLoS), 2022)
Improving breastfeeding practices is key to reducing child mortality globally. Sub-optimal exclusive breastfeeding rates may be associated with inadequate hospital-based postpartum breastfeeding support, particularly in resource-limited health settings such as Malawi. While almost all children in Malawi are breastfed, it is a concern that exclusive breastfeeding rates in Malawi are declining. The objective of this study is to understand postpartum breastfeeding support after delivery at Malawian hospitals from the perspectives of health workers and caregivers. We conducted a secondary analysis of a descriptive qualitative study on health worker and caregiver experiences of breastfeeding support at health facilities in southern Malawi as part of the Innovating for Maternal and Child Health in Africa Initiative. In-depth interviews following a semi-structured topic guide were conducted at three secondary-level district hospitals and one tertiary-level central hospital. Interviews were thematically analysed in NVivo 12 software (QSR International, Melbourne, Australia). We interviewed a total of 61 participants, including 30 caregivers and 31 health care workers. Participants shared the following themes: 1) a focus on early initiation of breastfeeding, 2) inadequate follow-up on breastfeeding practice, and 3) feasibility challenges and local solutions. There was an emphasis on early initiation of breastfeeding, which was challenged by maternal exhaustion after delivery. Study participants reported poor follow-up on breastfeeding practice after initial counselling and reacting to adverse outcomes in lieu of adequate monitoring, with a reliance on caregivers to follow-up on challenges. There was poor support for facility-based breastfeeding after initial counselling post-delivery, which revealed an overall neglect in hospital postpartum care for those considered to be in good health after initial assessment. We recommend the development of indicators to track continued facility-based breastfeeding, identify vulnerable infants at-risk of feeding problems, and strengthening care in postnatal wards, which is currently as neglected component of maternity care.